A África está em nós: contos africanos de Angola e Moçambique em Língua Portuguesa para o ensino de base intercultural - MENEGON, Patrícia Pinheiro (2015)
The general objective of this research is to investigate - in the context of interculturalism – the reading of African tales from Angola and Mozambique in Portuguese in the final grades of elementary school of basic education, in order to promote the intercultural education requested in the laws 10.639/03 and 11.645/08. Regarding its structure, this research is composed of four chapters. As regards its methodological approach, a documentary survey about the current legislation regulating the inclusion of African culture in the school daily plan of basic education as well as an analysis of the literature on its practices, processes and socio-cultural expressions were carried out. After observing classrooms of both educational institutions and proposing the reading of African tales in Portuguese (specifically: a tale from Angola and two tales from Mozambique), an analysis of data provided by questionnaires and feedback from the subjects involved in the research was held. Data collection was conducted through questionnaires in which we investigated the social profile of the subjects and their habits of reading in and out of school. The data generated by objective questions were treated with simple statistics. As to the subjective questions (regarding the relationships of meaning produced by students): they were analyzed and described from the views set out, seeking to achieve this research main goal. We concluded that new perspectives for research on main nuances that guide the study of the intercultural basic education supported by the practices and projects related to current legislation are open. In particular, those ones related to basic education to ensure intercultural education free of stereotypes.